Temporal analysis of water balance in a Sahelian City: implication for water management - Oriola, E. O.; Ifabiyi, I. P.; A. A, Mousafawou (Penerbit Universiti Kebangsaan Malaysia, 2017)
Water balance analysis is a valuable tool for assessing the general status of water resource availability and environmental comfort, particularly in the arid and the semi-arid regions. It also strengthens water management decision making. This research examines water balance in a Sahelian City (Niamey). Relevant meteorological and hydrology data of Niger Republic were captured. Descriptive and inferential statistics were used to analyze the data. Standard Deviation and Coefficient of Variation were employed to examine variation within the data set, Time Series to show a trend, and scattered plots for graphical presentation of results. Multiple Regression and Correlations adopted for relationships between variables and Warren and Lewis water balance equation for the water balance. The mean annual rainfall in Niamey was computed to be 516.38mm. The total annual water loss by evaporation was 3,906.5 mm. The result shows that the total annual water loss and mean annual runoffs were 3,906.5 mm and 11,600m2/sec respectively, the rainy season last for three months and dry season last for nine months. Variation of runoff in Niamey revealed that River Niger has two hydrological seasons of high water discharge from September to January and low water discharge between February and August. There is a positive linear correlation between evaporation and water balance on one hand and run off and water balance on the contrary. The study concludes that Niamey had water deficit and classified as drought-prone area. Therefore, there must be an effective and efficient water resource management to redress deteriorating hydrology condition in Niamey.